Russian and Chinese consumers' acceptability of boar meat patties depending on their sensitivity to androstenone and skatole. (November 2016) - Font-i-Furnols, M.; Aaslyng, M.D.; Backus, G.B.C.; Han, J.; Kuznetsova, T.G.; Panella-Riera, N.; Semenova, A.A.; Zhang, Y.; Oliver, M.A.
Abstract: The aim of this work was to study the sensitivity of Chinese and Russian female consumers to androstenone and skatole and to identify their preference for pork patties from entire male pigs compared with those from castrated pigs. One-hundred-twenty women in each country were enrolled. The sensitivity of the consumers to both compounds was tested using smell strips and triangular tests. Pairwise tests were performed comparing patties from castrated male pigs with patties from boars with different levels of androstenone and skatole. Approximately 70% of the Russian and 60% of the Chinese consumers were sensitive to skatole and 37% and 32% were sensitive to androstenone, respectively. Nevertheless, a higher percentage of sensitive Russian consumers compared to Chinese consumers disliked the smell of both compounds. In Russia, the consumers' preferences were higher for patties with low levels of both compounds, while no differences were found in China. In both countries, consumers who were sensitive to skatole also preferred patties with low levels of both compounds. Thus, the levels of androstenone and skatole affect boar patty preferences. Highlights: Skatole-sensitive female consumers represent between 60 and 70% of Chinese and Russian consumers. Androstenone-sensitive female consumers represent approximately 35% of Chinese and Russian consumers Androstenone and skatole affect the preferences of skatole-sensitive consumers. Androstenone and skatole mainly affect the preferences of Russian consumers.